2023
DOI: 10.1021/acs.chemmater.3c00269
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Performance and Stability of Red-Light-Emitting Diodes Using Guanidinium Mixed-Cation Perovskite Nanocrystals

Abstract: Halide perovskite nanocrystals (PNCs) exhibit growing attention in optoelectronics due to their fascinating color purity and improved intrinsic properties. However, structural defects emerging in PNCs progressively hinder the radiative recombination and carrier transfer dynamics, limiting the performance of light-emitting devices. In this work, we explored the introduction of guanidinium (GA + ) during the synthesis of high-quality Cs 1−x GA x PbI 3 PNCs as a promising approach for the fabrication of efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Because A‐cation (Cs + ) hardly contributes to the band–edge construction and radiative transition process, modifying A‐cation is supposed to become the effective approach to fine‐tune thermodynamic or kinetic stabilization, interfacial weak interactions, and surface functionalization. [ 8c,17 ] As our synthesis strategy has substantially reduced the proportion of Cs‐oleate and over‐feeding PbI 2 precursor, A‐cation defection ( V A ) is prospectively dominated in our CsPbI 3 QDs. As it is known, this composition‐dependent defect type is unlikely to degrade the optoelectronic properties of CsPbI 3 QDs, [ 18 ] and CsI‐terminations are considered as the major surface termination of CsPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Because A‐cation (Cs + ) hardly contributes to the band–edge construction and radiative transition process, modifying A‐cation is supposed to become the effective approach to fine‐tune thermodynamic or kinetic stabilization, interfacial weak interactions, and surface functionalization. [ 8c,17 ] As our synthesis strategy has substantially reduced the proportion of Cs‐oleate and over‐feeding PbI 2 precursor, A‐cation defection ( V A ) is prospectively dominated in our CsPbI 3 QDs. As it is known, this composition‐dependent defect type is unlikely to degrade the optoelectronic properties of CsPbI 3 QDs, [ 18 ] and CsI‐terminations are considered as the major surface termination of CsPbI 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The benets of guanidium cations are attributed to their strong hydrogen bonding ability with the surface halides, which in turn facilitates the surface defect recovery. [58][59][60][61] 3D/2D core/shell perovskites are regarded as multidimensional perovskites, where Chen et al revealed that the multidimensional type-I heterostructure formation between 3D MAPbBr 3 and 2D (octylammonium) 2 PbBr 4 leads to multiphoton absorption, which are useful for multiphoton imaging applications. 62 In a recent report by Ye et al, 25 spin-polarised luminescence behaviour has been studied, where a chiral organic ammonium bromide molecule is introduced to provide a 2D perovskite layer coating, which formed a 3D/2D core/shell with a type-II heterostructure.…”
Section: Semiconductor/semiconductor Heterostructurementioning
confidence: 99%
“…Metal halide perovskite materials with ABX 3 stoichiometry (for example, with A: CH 3 NH 3 + or Cs + , B: Pb 2+ , X: I – or Br – ) and their derivates such as double metal halide perovskites with A 2 BX 6 formulas have recently received significant attention, particularly for their demonstrated potential for photovoltaics and other optoelectronic applications. These materials have excellent properties like bandgap tunability, structural flexibility, and remarkable charge transport properties, resulting in excellent device performances. Power conversion efficiencies (PCEs) of lead-based perovskite solar cells (PSCs) reached up to 26.1% in 2023 equivalent to commercial solar cells and keep rising yearly . Furthermore, the affordability and accessibility of perovskite materials significantly encourage the development of the technology for commercial purposes .…”
Section: Introductionmentioning
confidence: 99%